Development of an Arduino-integrated STEM-based worksheet to improve biology undergraduate students’ scientific literacy - Aisyah Mardhotillah; Rinie Pratiwi Puspitawati; Pramita Yakub; Prasetyo Listiaji; Arini Zahrotun Nasichah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Several studies have reported that biology education students' scientific literacy in Indonesia remains low, with STEM learning offered as one solution. However, STEM implementation in higher education remains limited, particularly in biology education.  Objectives: This study aims to develop STEM-based worksheets that are valid, practical, and effective in improving scientific literacy skills. Methods: This study used a Research and Development (R&D) approach following the ADDIE model. It involved 36 first-year students in the Biology Education Program at Universitas Negeri Surabaya. Data were gathered through observation, questionnaires, and pre- and post-tests, then analyzed using paired t-tests, Cohen’s d effect size, and N-Gain. Results: The worksheet was rated valid with a score of 0.97, while the carbon dioxide detector scored 0.98 (validity). Practicality was rated at 99.81% (highly practical) by observers and 99.19% (highly practical) by students through questionnaires. A paired t-test with a two-tailed significance level (Sig.) of 0.00 < 0.05, showed a significant difference between pre-test and post-test scores. Cohen’s d effect size was 3.93 (very large), and N-Gain was 0.77 (high gain). Conclusion: STEM-based worksheets are valid, practical, and effective tools for improving students’ scientific literacy skills regarding respiratory rate.